Postdigitale Musikpädagogik im Plattformzeitalter. Über die konzeptionelle Rahmung einer Fortbildung für Lehrkräfte zur Rolle audiovisueller Kunst- und Vermittlungspraxis in postdigitaler Musikkultur - Godau, Marc; Gosmann, Phillip (Diskussion Musikpädagogik)

Die Dinge und der Musikunterricht - Godau, Marc (Handbuch Musikpädagogik: Grundlagen - Forschung - Diskurse)

Institutionalisierung der schulpraktischen Ausbildung im Ausland: Empirische Befunde zu Entwicklungen und Möglichkeiten neuer Wege in der Lehrer*innenbildung - Spiekenheuer, Mara; Freitag, Christine; Koch, Lea (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- Und Professionsentwicklung.)

Chancen und Herausforderungen des Krisenbegriffs zur Untersuchung historischen Lernens im bilingualen Geschichtsunterricht. Werkstattbericht eines Dissertationsprojekts - Pilz, Franziska (Geschichtslernen in Zeiten der Krise)

Muslim:innenfeindlichkeit und antimuslimischer Rassismus in Deutschland: Kategoriale Verstrickungen, Intersektionalität, Rassismuskritik und pädagogische Praxis - Diekmann, Isabell (Religiöse Diversität intersektional. Herausforderungen für die Lehrkräftebildung)

Improving the load-bearing capacity of clinched joints through cavity filling with structural epoxy adhesive. - Devulapally, Deekshith Reddy; Tröster, Thomas (Discover Mechanical Engineering)

Die missverstandene Princesse Jaune - Camille Saint-Saëns und der Japonismus - Jouenne, Zélie (Forschen und Lehren in der Historischen Musikwissenschaft)

Vielfalt als Ressource - Alles ein Frage der Haltung? - Meusel, Sarah; Albers, Timm (Kleinstkinder in Kita und Tagespflege)

Unterstützte Kommunikation - Eine Brücke zur Sprache - Albers, Timm; Jesuthasan, Jonitta; Meusel, Sarah (Kleinstkinder in Kita und Tagespflege)

Inklusion von Anfang an - Dabeisein ist nicht alles! - Albers, Timm; Jesuthasan, Jonitta; Meusel, Sarah (Kleinstkinder in Kita und Tagespflege)

Evi:P - Evaluationsinstrument für eine partizipative und inklusive Praxis in der Kindertagesbetreuung - Albers, Timm; Meusel, Sarah

Adolescents’ engagement with #fitspiration content—a systematic review of qualitative and quantitative studies and pedagogical implications for physical education Der Umgang von Jugendlichen mit Inhalten zu #fitspiration - Ein systematisches Review qualitativer und quantitativer Studien sowie pädagogische Implikationen für den Sportunterricht - Grimminger-Seidensticker, Elke; Korte, Johanna (German Journal of Exercise and Sport Research)
Abstract Social media is integral to adolescents’ daily lives and plays an important role in their health- and fitness-related behavior, particularly through trends such as #fitspiration, a portmanteau of “fit” and “inspiration.” This trend has become a prominent aspect of adolescents’ fitness culture. Empirical studies demonstrate that while #fitspiration holds the potential to motivate adolescents to be physically active, it also perpetuates gender-stereotyped, predominantly White, ableist, and normative body ideals associated with fitness and an idealized weight. This trend can be linked to an increased risk of body image concerns or disordered eating among adolescents. Understanding adolescents’ engagement with fitspiration content is crucial for tailoring health and media literacy education within physical education. Therefore, a systematic review of qualitative and quantitative studies was conducted. A search of five electronic databases yielded 312 abstracts, of which 12 met the inclusion criteria. The analysis of the selected studies was based on thematic analysis and included both primary and secondary data. Seven analytical themes emerged: (1) 37–56% of adolescents actively engage with fitspiration content on social media; (2) it fulfills their need for informal and accessible participation; (3) it fosters a sense of social connection; (4) they derive inspiration from peers and influencers; (5) they aspire to idealized body standards; (6) they seek quick solutions when dissatisfied with their bodies; and (7) a few become demotivated and critical when unable to achieve these ideals. Consequently, educators should balance the potential benefits with media literacy interventions to mitigate risks such as body image issues and eating disorders.

Does inflammation moderate the effect of vitamin D supplementation on depressive symptoms? Results of an interventional study in children and adolescents - Schlarbaum, Laura; Jankovic, Nicole; Bühlmeier, Judith; Hohoff, Eva; Dankers, Rhea; Engler, Harald; Hirtz, Raphael; Zwanziger, Denise; Grasemann, Corinna; Peters, Triinu; Hinney, Anke; Antel, Jochen; et al. (European Journal of Nutrition)

Volume Quantization with Flexible Singularities for Hexahedral Meshing - Brückler, Hendrik; Campen, Marcel (Computer Graphics Forum)
Abstract We present a novel algorithm for quantization and subsequent hexahedral mesh generation from seamless volumetric maps. Quantization is the process of choosing integers that represent the numbers of hexahedral elements to be placed in each region of the volume, and transforming the seamless map into an integer‐grid map matching that choice, inducing a hexahedral mesh. Previous work computes such quantizations under the restriction of a fixed predetermined singularity graph. Our novel approach allows for implicit modification and, in particular, simplification of the map's singularity structure wherever that benefits the chosen objective, such as matching target hexahedron sizes as closely as possible. It comes with two novel ingredients: A feature‐focused distortion measure guiding the quantization, and constraints ensuring map injectivity and structure preservation of geometric and topological features, both without relying on a fixed singularity structure. We demonstrate the benefit of the added flexibility offered by this approach: it allows for the generation of hexahedral meshes that more accurately match a desired resolution globally, as well as of meshes exhibiting a simpler block structure.

Focus. La rue de Brabant ou la rue de Bavière, vestiges d'un souverain 'étranger`aux Pays-Bas espagnols - Huybrechts, Yves (Les noms de lieux à Bruxelles. Enjeux passés et présents)

(Berufs-)Bildung im Wandel der Gesellschaft. Brüche und Kontinuität in Veränderungsprozessen und ihre Konsequenzen für das (Berufs-)Bildungssystem - Daniel-Söltenfuß, Desiree; Kremer, H.-Hugo; Kückmann, Marie-Ann

Identification of multiple steady states in reactive absorption columns equipped with structured packings - Franke, Patrick; Lutters, Nicole; Riese, Julia; Kenig, Eugeny

Umgang mit (Um-)Brüchen – ein Normalzustand? Gestaltung von Innovationsprozessen aus Sicht des beruflichen Bildungspersonals - Breuing, Friederike; Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

Vollständige Bestimmung der akustischen Materialparameter von Polymeren II - Dreiling, Dmitrij; Itner, Dominik; Birk, Carolin; Gravenkamp, Hauke; Henning, Bernd
In diesem Forschungsprojekt wurde ein Messverfahren zur Bestimmung akustischer Materialparameter von Polymeren im Ultraschallfrequenzbereich entwickelt. Das Verfahrens sollte, die üblichen standardisierten Prüfmethoden erweitern, die bislang primär im quasistatischen oder niederfrequenten Bereich eingesetzt wurden. Im Gegensatz zu bestehenden Verfahren wie dem Zeitstandversuch oder der Dynamisch Mechanischen Analyse (DMA) nach [DIN6721] sollte die neue Methode eine nicht-invasive Charakterisierung der (visko-)elastischen Materialparameter im Frequenzbereich von 0,75 MHz bis 2,5 MHz ermöglichen. Das entwickelte Ultraschallmesssystem arbeitet nach dem Puls Echo-Prinzip und kann eine räumlich segmentierte, ringförmige Anregung erzeugen. Die Bestimmung der frequenzabhängigen Materialparameter geschieht hierbei über ein inverses Verfahren. Die Ergebnisse des Projekts zeigen, dass die Segmentierung der Anregung, die Geometrie der Probe sowie das Puls-Echo-Messprinzip die Messergebnisse sowie die Sensitivität gegenüber Scherparametern wesentlich beeinflussen. Im Rahmen des Projektes wurde auch eine statistische Auswertung des Optimierungsverfahrens hinsichtlich transversal-isotroper Materialsymmetrie mit Rayleigh-Dämpfung durchgeführt. Die Ergebnisse zeigen, dass das entwickelte Verfahren gute Konvergenzeigenschaften aufweist und sich durch verbesserte Robustheit auszeichnet.
Keywords: Materialcharakterisierung; Polymer; Inverses Problem; Ultraschall; Optimierung

Cascaded Metasurface Interferometer for Multipath Interference with Classical and Quantum Light - Aschwanden, Rebecca; Claro-Rodríguez, Nicolás; Zhao, Ruizhe; Kallert, Patricia Anna Maria; Krieger, Tobias; Buchinger, Quirin; Covre da Silva, Saimon F.; Stroj, Sandra; Rota, Michele; Höfling, Sven; Huber-Loyola, Tobias; Rastelli, Armando; et al. (ACS Photonics)
Beamsplitters represent fundamental components in both classical and quantum optical systems, enabling the distribution of light, as well as the generation of interference, superposition, and entanglement. However, optical networks constructed from conventional bulk 2 × 2-beamsplitters encounter inherent scalability issues, as the number of required beamsplitters scales quadratically with the number of optical modes for a fully connected network. Metasurfaces offer a promising route to overcome these constraints. By manipulating light at the wavelength scale, compact optical components with advanced functionalities can be constructed, which address several modes simultaneously. In this work, we design and experimentally utilize a metasurface as a multiport beamsplitter. Furthermore, we realized a multimode interferometer composed of two cascaded metasurfaces. We characterize the individual and cascaded metasurfaces by using classical light, showing controllable splitting ratios through tunable phase relations. We then expand the approach to quantum light, employing single photons to demonstrate second- and third-order photon correlations as well as single photon interference across multiple spatial paths. These results establish metasurface-based multiport beamsplitters as a scalable and reconfigurable platform bridging classical and quantum photonics.
Keywords: metasurface; beamsplitter; interferometer; quantum network; single photons; nanophotonics